Foreign exchange exposure management : a portfolio approach - Soenen, Luc A. (Alphen aan den Rijn ; Germantown, Maryland : Sijthoff & Noordhoff, 1979)
This books focusses on the hedging of currency portfolio as specified as a decision problem, with the company's exposure as input together with spot and forward exchange rates, the future spot rates of the currencies in the portfolio as unknown random variables, and the amounts to be hedged per currency as decision variables.
Includes index.
Includes bibliographical references: p. 135-139.
osa 19/06/2017
Loans
Keywords: International business enterprises; Foreign exchange administration; Hedging (Finance).; Portfolio management